Upward Comparison at the Workplace: A Review - Rosita Yuniati; Charli Sitinjak (East Asian Journal of Multidisciplinary Research, 2022)
The study of workplace envy has gained popularity in recent years. The goal of this paper is to examine and systematize the knowledge regarding envy and envy at work that has been offered by empirical research in the last five years, based on a prior review. 32 papers were chosen after searching scientific databases, defining exclusion and inclusion criteria, and classifying the material. The findings reveal an increasing interest among researchers in examining benign envy and its implications, as well as investigating novel variables to explain envy in the workplace. The two main theoretical frameworks employed in the studies reviewed are social comparison theory and cognitive appraisal theory. Researchers can use the findings of this study to develop future studies and devise intervention measures to reduce workplace envy.